Do judges react to the probability of appellate review? Empirical evidence from trial court procedures - Michael Berlemann; Robin Christmann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
The appellate review system is intended to serve as an efficient remedy for imperfect judicial decision making. However, it can fulfill this task only when appeals are filed solely due to bad verdicts and are ex-ante unpredictable based on factors that are exogenous to the judge. Using data from case records of a German trial court, we show that the probability of appeal can be predicted based on easily observable exogenous factors. Controlling for the complexity of a legal case, we find that judges also tend to increase their effort when the ex-ante probability of appeal is high. Thus, our empirical evidence indicates an inefficiency in the appellate review system.
Keywords: K10; K41; D82; 330; litigation; judicial behavior; appellate review; civil procedure